2020
DOI: 10.3390/antibiotics9060315
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities and Challenges for Improving Anti-Microbial Stewardship in Low- and Middle-Income Countries; Lessons Learnt from the Maternal Sepsis Intervention in Western Uganda

Abstract: This paper presents findings from an action-research intervention designed to identify ways of improving antimicrobial stewardship in a Ugandan Regional Referral Hospital. Building on an existing health partnership and extensive action-research on maternal health, it focused on maternal sepsis. Sepsis is one of the main causes of maternal mortality in Uganda and surgical site infection, a major contributing factor. Post-natal wards also consume the largest volume of antibiotics. The findings from the Maternal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 16 publications
(16 reference statements)
0
9
0
Order By: Relevance
“…The NAP emphasizes the need to strengthen the evidence base on antimicrobial use to inform policy including through research [ 9 ]. However, most of the research on AMS in the country to date has been from large health facilities [ 27 29 ], with minimal literature from community settings. Given that AMR is a complex public health problem that concerns many sectors, there is need for more evidence on access and use of antimicrobials among humans and animals particularly in the community, as well as disposal of antimicrobials at household level.…”
Section: Introductionmentioning
confidence: 99%
“…The NAP emphasizes the need to strengthen the evidence base on antimicrobial use to inform policy including through research [ 9 ]. However, most of the research on AMS in the country to date has been from large health facilities [ 27 29 ], with minimal literature from community settings. Given that AMR is a complex public health problem that concerns many sectors, there is need for more evidence on access and use of antimicrobials among humans and animals particularly in the community, as well as disposal of antimicrobials at household level.…”
Section: Introductionmentioning
confidence: 99%
“…Kiryandongo district is one of the 146 districts in Uganda [16]. The district has thirty-nine (39) health facilities constituting of twenty-one (21) Government, fourteen (14) Private for Profit and four (4)-Private not for profit (PNFP). These facilities serve the population of Kiryandongo and the surrounding districts of Masindi, Nakasongola, Oyam, Apac, Amuru and Nwoya.…”
Section: Study Settingmentioning
confidence: 99%
“…Despite the tremendous achievements accrued by the implementation of laboratory quality management system initiatives in Uganda, laboratory services still face challenges including stock out of health commodities, inadequate human resource, limited testing scopes and inadequate funding [13,14]. These challenges compromise health care performance, and attainment of national and international goals.…”
Section: Introductionmentioning
confidence: 99%
“…A study of post-operative sepsis cases in rural Eastern Uganda [35] reported 14 % S. aureus isolates to be resistant to five different classes of antibiotics and 3 % resistant to six different classes [35]. Whilst the Ugandan national action plan (UNAP) reports prevalence of MRSA in healthcare settings at 2-50 % [23], the WHO AMR global report on surveillance (2014) found overall MRSA prevalence to range from 12-80 % across Africa and to exceed 20 % in all six WHO regions [36]. There have been reports of more than 80 % MRSA prevalence in African, American and Western Pacific regions [36].…”
Section: Antibiotic Susceptibility Testing (Ast) At Fprrhmentioning
confidence: 99%
“…This study is part of a multi-disciplinary intervention at FPRRH linking laboratory testing with training of health professionals in understanding common drivers of AMR aiming to reduce unnecessary and ineffective use of antibiotics in line with the UNAP [ 23 ]. We combine existing hospital AST data with whole genome sequencing to investigate antibiotic resistance profiles, population structure and virulence gene carriage of S. aureus isolated from a range of infection sites including wounds, blood, and the urinary tract, in a region with little previous published data, towards better informed treatment practice and infection/AMR control policies.…”
Section: Introductionmentioning
confidence: 99%